Bilateral Tubo-Ovarian Abscesses Four Years After Total Abdominal Hysterectomy - L. E. Mendez; S. M. Bhoola; I. R. Horowitz (Hindawi Limited, 1998)
Background: Pelvic inflammatory disease (PID) is a common gynecologic disorder. One known complication of PID is tubo-ovarian abscess (TOA) formation. The predominant theory on TOA formation postulates that an ascending infection from the cervix through the uterus to the fallopian tubes and ovaries results in abscess formation. Other theories include seeding via a hematogenous infection, diverticular disease, and appendicitis.